2021
DOI: 10.21037/atm-20-4895
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled pulmonary vasodilators: a narrative review

Abstract: Pulmonary hypertension (PH) is a severe disease that affects people of all ages. It can occur as an idiopathic disorder at birth or as part of a variety of cardiovascular and pulmonary disorders. Inhaled pulmonary vasodilators (IPV) can reduce pulmonary vascular resistance (PVR) and improve RV function with minimal systemic effects. IPV includes inhaled nitric oxide (iNO), inhaled aerosolized prostacyclin, or analogs, including epoprostenol, iloprost, treprostinil, and other vasodilators. In addition to pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 197 publications
(174 reference statements)
0
15
0
1
Order By: Relevance
“…pH in blood gas analysis 4h after commencement of iNO was determined to be significantly increased in reduction in the FiO2 by 20% within 3h of commencing iNO therapy were defined as "positive responders'' and those in which FiO2 increased, remained unchanged or reduced by <20% were defined as "negative responders". If clinical response was not observed to hypoxemia, the dose of iNO was increased to 40 ppm, since NO improvement to oxygenation is largely dose dependent and higher doses of iNO (20-80ppm) may cause progressive pulmonary vasodilatation (15)(16)(17). Blood gases and levels of methemoglobin were analyzed prior to initiation of iNO therapy and every 4h thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…pH in blood gas analysis 4h after commencement of iNO was determined to be significantly increased in reduction in the FiO2 by 20% within 3h of commencing iNO therapy were defined as "positive responders'' and those in which FiO2 increased, remained unchanged or reduced by <20% were defined as "negative responders". If clinical response was not observed to hypoxemia, the dose of iNO was increased to 40 ppm, since NO improvement to oxygenation is largely dose dependent and higher doses of iNO (20-80ppm) may cause progressive pulmonary vasodilatation (15)(16)(17). Blood gases and levels of methemoglobin were analyzed prior to initiation of iNO therapy and every 4h thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence indicates that ILO administration may be associated with systemic vasodilation and inhibition of platelet aggregation [ 15 ]. Indeed, we frequently observed hypotension during OLV in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that once OLV was initiated, the patients’ level of Qs/Qt declined compared to before, which is consistent with the previous research. Inhaling PEG1, a kind of selective pulmonary artery dilator, by ultrasonic atomization during OLV could dilate the pulmonary artery, which causes stealing blood from the shunt area to the non-shunt area, reducing intrapulmonary shunt [ 21 , 22 ]. In addition, a previous study demonstrated that PGE1 could decrease pulmonary shunt and increase PaO 2 in a dose-dependent manner during OLV [ 11 ].…”
Section: Discussionmentioning
confidence: 99%